Fungi mediated production and practical purification of (R)-(-)-3-quinuclidinol - Kolet, Swati P.; Jadhav, Dipesh D.; Priyadarshini, Balaraman; Swarge, Bhagyashree N.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2014)
A fungal system belonging to Mucoraceae family (Mucor piriformis) was explored for the asymmetric reduction of a prochiral ketone, 3-quinuclidinone (I) in an efficient manner to produce an important pharmaceutical precursor (R)-(-)-3-quinuclidinol (II) with similar to 96% enantiomeric excess. The efficiency of the process was improved by developing a cation exchange resin (Amberlite IR-120) which assisted the purification of water soluble metabolite II from fermentation media. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: (R)-(-)-3-Quinuclidinol; Amberlite IR-120; Biotransformation; Ion exchange resin; Mucor pinformis

Fungal mediated kinetic resolution of racemic acetates to (R)-alcohols using fusarium proliferatum - Jadhav, Dipesh D.; Patil, Harshal S.; Chaya, Patil S.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2016)
Fungal mediated kinetic resolution of seven acyclic/aromatic acetates was achieved using Fusarium proliferatum to furnish (R)-alcohols in high enantiomeric excess (>95%). The kinetic resolution was established as one-pot two-step de-esterification/oxidation biocatalytic process. Further, the preparative scale synthesis of (R)-(+)-1-phenylethanol was accomplished through de-esterification/oxidation of (+/-)-1-phenylethyl acetate using the whole cell of F. proliferatum NCIM 1105. (C) 2016 Elsevier Ltd. All rights reserved.